Implementation of the Trisikkha Plus Learning Management Model to Enhance the Characteristics of Good Citizenship for Vocational Certificate Students - Kittipat Srichai; Montree Wongsaphan (Journal of Educational Issues, 2024)
Trisikkha principles consisting of morality, concentration, and wisdom discovered by the Lord Buddha, as well as the concept of contemplative education has been applied to learning-teaching management in Thailand for a long time. This research aimed to investigate the implementation of the learning management model based on the Trisikkha principles together with the concept of contemplative education to enhance the characteristics of good citizenship for vocational certificate students of Buriram Polytechnic College, Thailand. The data were collected by means of an evaluation form on characteristics of good citizenship, a learning achievement test, and a students’ satisfaction questionnaire which were employed to twenty-nine students. The descriptive statistics applied to analyze data were mean, standard deviation, and t-test. The results of the study indicated that the students had higher characteristics of good citizenship. In addition, their learning achievement after learning was significantly higher than before learning at the .05 level. Moreover, the overall satisfaction toward the model was at a high level.